PENINGKATAN MOTIVASI BELAJAR MELALUI IMPLEMENTASI MODEL CONCEPT LEARNING TIPE MAKE A MATCH PADA MATAPELAJARAN PPKn - Meliana Meliana; Kokom Komalasari (Universitas Sriwijaya, 2019)
abstract: This research was conducted in class X.MIPA.5 SMA Negeri 6 Bandung, in the first semester of 2017/2018 Academic Year with a total of 34 students. This PTK data collection technique uses observation, interviews, documentation and field notes. Conducting research with a process cycle of activities in classroom action research beginning with planning (planning), applying (action), observing and evaluating the process and results of the action (observation and evaluation), reflecting (reflection), then returning to the planning stage of action until quality is achieved desired learning. In the first cycle of action I with the number of subjects amounted to 33 people with observation techniques both teacher categories with a score of 117 and the percentage of 71.34% while observing the activities of students categorized sufficiently with a score of 80 and a percentage of 50%. Then the motivation of students in the first cycle with a score of 194 percent 36.74% less category. Cycle II with the number of subjects amounted to 32 people with very good category of observation techniques for teachers with a score of 143 and a percentage of 87.21% while the observation of the activities of students was categorized both with a score of 103 and a percentage of 64.38%. Then the motivation of students in the second cycle with a score of 294 percentage of 57.42% good categories. Cycle III with the number of subjects amounted to 32 people with observation techniques on the category of very good teachers with a score of 136 and a percentage of 87.21% while observations of the students were categorized very well with a score of 136 and a percentage of 85%. Then the motivation of students in cycle III with a score of 401 percentage 78.32% of the category is very good. From the results of data management there is a significant increase in student motivation, namely the comparison of students' motivation in cycles I, III, III, namely 50%, 64.35 and 85%. So there is an increase in learning activities and motivation of students before and after the implementation of the concept learning model make a match type in the subjects. Keywords: Type make a match, Pancasila Education, Student Motivation